Immanuel Kant : observations on the feeling of the beautiful and sublime and other writings - Kant, Immanuel, 1724-1804.; Frierson, Patrick R., 1974-; Guyer, Paul, 1948- (Cambridge ; New York : Cambridge University Press, 2011)
"This volume collects Kant's most important ethical and anthropological writings from the 1760s, before he developed his critical philosophy. The materials presented here range from the Observations, one of Kant's most elegantly written and immediately popular texts, to the accompanying Remarks which Kant wrote in his personal copy of the Observations and which are translated here in their entirety for the first time. This edition also includes little-known essays as well as personal notes and fragments that reveal the emergence of Kant's complex philosophical ideas. Those familiar with Kant's later works will discover a Kant interested in the 'beauty' as well as the 'dignity' of humanity, in human diversity as well as the universality of morals, and in practical concerns rather than abstract philosophizing. Readers will be able to see Kant's development from the Observations through the Remarks towards the moral philosophy that eventually made him famous"--
"The main objective of Cambridge Texts in the History of Philosophy is to expand the range, variety, and quality of texts in the history of philosophy which are available in English. The series includes texts by familiar names (such as Descartes and Kant) and also by less well-known authors. Wherever possible, texts are published in complete and unabridged form, and translations are specially commissioned for the series. Each volume contains a critical introduction together with a guide to further reading and any necessary glossaries and textual apparatus. The volumes are designed for student use at undergraduate and postgraduate level, and will be of interest not only to students of philosophy but also to a wider audience of readers in the history of science, the history of theology, and the history of ideas"--
Machine generated contents note: Introduction; Chronology; Further reading; Note on the texts; Thoughts on the Occasion of Mr Johann Friedrich von Funk's Untimely Death (1760); Observations on the Feeling of the Beautiful and Sublime (1764); Remarks in Observations on the Feeling of the Beautiful and Sublime (1764-5); Essay on the Maladies of the Head (1764); Inquiry concerning the distinctness of the principles of natural theology and morality (1764); M. Immanuel Kant's announcement of the programme of his lectures for the winter semester, 1765-6 (1765); Herder's Notes from Kant's Lectures on Ethics (1762-4); Selected notes and fragments from the 1760s; Index.
Includes bibliographical references and index.
Keywords: Philosophy; Aesthetics